Accessibility Expectations of Tourists with Disabilities in National Parks. Issue 1 (2nd January 2019) - Chikuta, Oliver; du Plessis, Engelina; Saayman, Melville
ABSTRACT: This study sought to establish the expectations of people with disabilities when they visit national parks. The study has been motivated by the gap between the increasing numbers of people with disabilities worldwide who travel and the adequacy of tourism facilities, especially nature-based tourism facilities for people with disabilities. It was further stimulated by the fact that most of the accessibility standards in existence today have been formulated by policymakers without any consultations with the affected persons. The aim of the study was to develop research-based guidelines to help park management in product development. The study adopted a mixed method approach of both qualitative and quantitative data collections. It also took a cross-dimensional approach by including different dimensions of disabilities in order to get a more balanced view of the expectations of people with disabilities in national parks. The findings of this study revealed that people with disabilities, regardless of their type of disabilities regard employee attitudes highly. They are more worried about the way people treat them than the physical access. It was established that steps and staircases are highly discouraged by people of all embodiments. A set of recommendations was given to inform policy on universal accessibility.